TEACHING CONVERSATION IN ENGLISH LANGUAGE CLASSROOM: CONVERSATIONAL TECHNIQUES - Milova Оksana Ye. (Educological discourse, 2015)
This article deals with the theoretical analysis of teaching conversation which is based on real-life situations and develops learners’ conversational skills in English language classroom. Teaching conversation is the highest and a creative phase of language learning process. It is characterized by “interacting”. Accordingly, the principles and “steps” of teaching conversation by means of using various conversational techniques are described in the article. In order to achieve the aim of development learners’ conversational skills, teachers should use special conversational techniques such as small-group discussions, role-plays, simulations, improvisations, debates, brainstorming, reporting, interviews and others. Therefore, the performing procedures of some of the techniques (small-group discussions, role-plays, improvisations, debates) are analyzed in the article.